HUMAN RESOURCE DEVELOPMENT PRODUCTIVE TEACHER OF SMK PALU CITY AT THE CENTRAL SULAWESI PROVINCIAL EDUCATION OFFICE - Yudiawati Vidiana Windarrusliana; Daswati Daswati; Muhtar Lutfi; Jamaluddin Jamaluddin (Program Studi PGSD Universitas Flores, 2026)
This study originates from the issue of weak human resource development (HRD) among productive teachers in Palu City, characterized by an imbalance between the number of productive teachers and the ideal needs, resulting in a heavy workload that diminishes motivation for self-development. The comfortable status of teachers as civil servants and their financial stability through regular salaries and professional allowances further weaken both internal and external incentives to improve competencies. In contrast, the absence of economic incentives, rewards, or sanctions related to professional development activities reduces teachers’ commitment to responding to the evolving demands of vocational education. The study aims to analyze HRD among productive teachers using Swanson’s theoretical framework, which consists of three levels of analysis: individual, process, and organizational. A qualitative approach is employed to understand how individual motivation, capacity, readiness to develop, learning processes, and organizational policies influence teachers’ competency development. The findings indicate that the application of Swanson’s framework has not operated effectively due to fundamental weaknesses at the individual level, which hinder the optimal functioning of learning processes and organizational support. Overall, HRD among productive teachers in Palu City has not aligned with Swanson’s principles, highlighting the need for policy interventions in teacher staffing, strengthened professional development incentives, and the cultivation of an organizational culture that promotes continuous learning.